Desoneraç\~ao fiscal de n\~ao residentes e a estrutura a termo da taxa de juros: Efeito da medida provisória no. 281/2006 - Katia Rocha; Ajax Moreira (Instituto de Pesquisa Econômica Aplicada (IPEA), 2009)
– This study analyzes the effect of the Provisional Measure 281, published at 16/02/2006 and converted in the Law no 11.312, at 27/06/2006, which reduced to zero the income tax of federal bonds achieved by non-residents, over the Brazilian term structure of interest rate. We used the daily indicative yield rate provided by Andima from fixed (LTN and NTN-F) and floating (NTN-B) bonds, as well as the respective duration in the period of January 2005 to December 2007. The methodology approximates the term structure by linear combinations of the Laguerre and Legendre polynomials and uses several specification models and controlling variables to isolate the effect of the Provisional Measure over the term structure evolution. The findings show that one cannot reject the effect resulting from the fiscal tax reduction. Statistically significant and robust results indicate a decrease of 150 basis point in the short-term interest, and an unexpected increase of similar figure in the long-term interest, possible explained by changes in the supply of the federal government bonds.
Keywords: E43; E65; G14; 330